Gugatan pelanggaran asas-asas umum pemerintahan yang Baik setelah berlakunya UU Administrasi Pemerintahan melalui PTUN Yogyakarta - Eny Kusdarini (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
An unfair administrative decision considering by individuals or private corporates subject to be dismissed through Public Administrative Courts. This essay was written based on research conducted during September 2016 on the final and executable judge’s decision after issuing  Governmental Administration Law regulating the good government principles. This research was conducted by identifying the final and executable judge’s decision after issuing Governmental Administration Law at Public Administration Court on October 2016. Considering that based on this law, article 10 verse (1) contains the Good Governance Principles, namely: certainty due to law, utility, impartial, thoughtful, non-abuse principle, transparency, public interest first, and public service were applied as long as considered by judge expressed on the final and executable judge’s decision. Therefore, hopefully after the enactment of the law judge on Public Administrative Court should apply these principles on judicial practices. Hopefully, this essay can be considered as an input to revise the law as well as additional materials teaching on good governance among University Lecturer.